2011
DOI: 10.1007/s00394-011-0218-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of 1α,25-dihydroxycholecalciferol on MCP-1 and adiponectin production in human white adipocytes

Abstract: DHCC attenuates MCP-1 and adiponectin production in human adipocytes, thereby reducing the expression of both pro- and anti-inflammatory factors. These effects may explain the difficulties so far in determining the role of DHCC in insulin sensitivity and obesity in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 45 publications
(47 reference statements)
6
57
2
Order By: Relevance
“…23 Most likely, the hydroxylation of VD in AT is of importance to AT itself, as it allows for autocrine/ paracrine actions of VD. 54,55 Our findings of differential expression of the VDR and CYP27B1 in lean and obese women warrants further investigations on the autocrine/paracrine actions of VD in different compartments of AT.…”
Section: Discussionmentioning
confidence: 82%
“…23 Most likely, the hydroxylation of VD in AT is of importance to AT itself, as it allows for autocrine/ paracrine actions of VD. 54,55 Our findings of differential expression of the VDR and CYP27B1 in lean and obese women warrants further investigations on the autocrine/paracrine actions of VD in different compartments of AT.…”
Section: Discussionmentioning
confidence: 82%
“…These results have since been challenged by several groups (67,(75)(76)(77) who consistently report anti-inflammatory effects of 1,25 (OH) 2 D whatever the model studied, which fits better with the well-described anti-inflammatory effect of VD in many other cell types (78) . Indeed, it was shown that 1,25(OH) 2 D significantly decreased the release of IL-8, monocyte chemoattractant protein (MCP)-1 and IL-6 by human preadipocytes (76) and MCP-1 by human adipocytes (75) . These anti-inflammatory effects were associated with inhibition of the NF-κB signalling pathway (77) .…”
Section: Regulation Of Inflammationmentioning
confidence: 79%
“…Indeed, several studies have reported the impact of VD on inflammation, with some discordance. Initial studies investigating the effects of VD on adipocytes (from murine and human origin) reported a proinflammatory effect (13,14), whereas several other studies have reported an antiinflammatory effect of VD on adipocytes (15)(16)(17)(18), consistent with the anti-inflammatory effect of VD in many other cell types (19).…”
mentioning
confidence: 83%
“…Indeed, 1,25(OH) 2 D (the active form of vitamin D) significantly decreased the release of IL8, CCL2 and IL6 in human preadipocytes (16) and CCL2 in human adipocytes (15) induced through proinflammatory stimuli, such as macrophage-conditioned medium, TNF␣ and IL1␤. In addition, 1,25(OH) 2 D decreased the preadipocyte-induced monocyte migration of THP-1 monocytes (16).…”
mentioning
confidence: 99%